Obtenção de nanopartículas de PMMAbPDMAEMA para sistemas de liberação controlada de moléculas bioativas - Engelmann, Klauss [UNIFESP] (2018)
The combination of PMMA, a polymer soluble in organic solvents, and with the watersoluble PDMAEMA, generates an amphiphilic copolymer with pHdependent properties and tendency to form micelles. The aim of this work is to obtain and characterize nanoparticles (NPs) of this copolymer to transport plasmid DNA into HEK 293T cells as a way to demonstrate its efficiency for gene transfection The methodologies tested for the preparation of NPs were adapted emulsification with evaporation of solvent, salting out and nanoprecipitation. The characterization of NPs was done by size and zeta potential (PZ) measurements, FTIR spectra analysis and DSC studies of the obtained suspensions. Rhodamine 6G (Rd6G) was encapsulated to be used in superresolution SR GSD 3D microscopy studies. For stability tests, NPs suspensions were kept at 37 °C and monitored for 30 days. The nanoprecipitation method was the most efficient to prepare NPs with no loss of mass, yielding NPs sized between 60100 nm and PZ from 20 to 30 mV. The FTIR showed the same profile for the polymer and the NPs. The stability studies monitoring the size and ZP of the particles showed that the NPs in aqueous medium are stable for 30 days. GSD microscopy shows the presence of fluorescent NPs with spherical characteristics. They also indicate that the balanced profile systems of the hydrophilic and hydrophobic fractions of the copolymers is important in their application as a DNA carrier. Nanoprecipitation was the best methodology to obtain PMMAbPDMAEMA NPs. The 1: 1 and 2: 1 copolymer NPs were shown to be more efficient at application as Plasmidial DNA transfection agents in systems with HEK 293T cell type